Ways to Improving Milk Production and Processing in Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article explores the challenges and opportunities in Uzbekistan's dairy sector, focusing on strategies to enhance milk production and processing. The current state is characterized by traditional farming practices, limited infrastructure, and untapped potential for technological advancements. Key solutions include adopting modern milking systems, precision feeding, and sustainable farming practices to improve productivity and animal welfare. The integration of advanced processing technologies such as pasteurization and rigorous quality control is essential to meet both domestic and international market demands. Furthermore, fostering collaborations among stakeholders – farmers, government bodies, and research institutions – can drive innovation and ensure sustainable growth. By addressing these areas, Uzbekistan has the potential to transform its dairy industry, boost economic growth, improve food security, and compete in global markets.